2023
DOI: 10.1186/s40729-023-00495-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the clinical safety and performance of a narrow diameter (2.9 mm) bone-level implant: a 1-year prospective single-arm multicenter study

Christian Walter,
Keyvan Sagheb,
Sebastian Blatt
et al.

Abstract: Purpose Narrow-diameter implants facilitate single‐tooth restoration when interdental or inter-implant spaces and bone volume are inadequate for using standard diameter implants. This study reports the short-term data on the clinical safety and performance of a bone-level-tapered two-piece implant with a 2.9 mm diameter in the clinical practice setting. This study was retrospectively registered on March 1st, 2016 (NCT02699866). Methods Implants wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
1
1
Order By: Relevance
“…Overall, the 3-year results are consistent with those published after 12 months of loading: more specifically, no additional implants were lost underlining the reliability of both implants for tooth replacement in single-unit gaps not also in the midterm. Our results are slightly better than those recently published by Walter et al 13 who reported an implant survival rate of 92.7% at 1 year after placement of 41 2.9 mm diameter implants. Possible explanations could be found in the differences in inclusion and exclusion criteria, the use of such an implant in different clinical scenarios (i.e., maxillary and mandibular incisors) and the fact that all patients in the present study were young and healthy.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…Overall, the 3-year results are consistent with those published after 12 months of loading: more specifically, no additional implants were lost underlining the reliability of both implants for tooth replacement in single-unit gaps not also in the midterm. Our results are slightly better than those recently published by Walter et al 13 who reported an implant survival rate of 92.7% at 1 year after placement of 41 2.9 mm diameter implants. Possible explanations could be found in the differences in inclusion and exclusion criteria, the use of such an implant in different clinical scenarios (i.e., maxillary and mandibular incisors) and the fact that all patients in the present study were young and healthy.…”
Section: Discussioncontrasting
confidence: 81%
“…12 Very recently, the clinical safety and performance of 2.9 mm NDIs in different clinical scenarios (i.e., maxillary and mandibular incisors) was documented by Walter and co-workers in a multicenter study reporting a 92.7% of implant survival rate after 1 year of loading. 13 Focusing on mid-term outcomes (i.e., with a follow-up of 3 years), satisfactory results have been published in two prospective clinical studies on NDIs with 3.0 mm 14 and 3.3 mm, 15 respectively. However, due to the lack of a control group and the limited number of patients included, the overall validity of the data obtained could be questioned.…”
Section: Introductionmentioning
confidence: 99%